2020
DOI: 10.1016/s2352-4642(20)30131-0
|View full text |Cite
|
Sign up to set email alerts
|

Promoting healthy movement behaviours among children during the COVID-19 pandemic

Abstract: Background: Healthy child and youth development is fostered through su cient physical activity (PA; including time outdoors), limiting sedentary behaviours (SB), and adequate sleep; collectively known as movement behaviours. Though the COVID-19 virus outbreak has changed the daily lives of children and youth, it is unknown to what extent related restrictions may compromise the ability to play and meet movement behaviour recommendations. This study examined the immediate impacts of COVID-19 restrictions on move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
292
2
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 291 publications
(340 citation statements)
references
References 10 publications
20
292
2
26
Order By: Relevance
“…These ndings are the rst to con rm speculations that pandemic-related restrictions are unfavourably related to movement behaviours of children and youth. 12,24 This observation has triangulated support from quantitative (descriptive and correlational) and qualitative (contextual) evidence.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…These ndings are the rst to con rm speculations that pandemic-related restrictions are unfavourably related to movement behaviours of children and youth. 12,24 This observation has triangulated support from quantitative (descriptive and correlational) and qualitative (contextual) evidence.…”
Section: Discussionmentioning
confidence: 64%
“…31 There are emerging calls bringing attention to the likely impact of the global pandemic on the movement behaviours of adults, children and youth. 12,32,33 Our ndings describe some of the ways Canadian parents are adapting to this challenge. In the open-ended questions, respondents of this survey identi ed several creative ways that they were using their leisure-time to develop or renew new family hobbies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Children's daily routine and healthy movement were affected by school closures. 35 A longitudinal observational study in Italy suggested that the obese kids underwent unfavorable changes in dietary habits, increased sleep and screen time, and decreased participation in outdoor activities during the COVID-19…”
Section: Lifestyle Behaviorsmentioning
confidence: 99%